Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Penghindaran Pajak (Studi Kasus Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022) - Harjo, Dwikora (JAMBIS : Jurnal Administrasi Bisnis, 2023)
Tax Avoidance is a strategic approach implemented by companies to minimize their tax burden while remaining compliant with relevant Tax Regulations. The purpose of this research was to analyze the effect of profitability and firm size on Tax Avoidance in mining companies listed on the Indonesia Stock Exchange in 2018-2022. Employing a descriptive quantitative method, the sample is determined using a purposive sampling technique to select a sample of 14 Companies that meet pre-defined criteria. The collected data will be subjected to analysis using IBM SPSS Statistics 25, encompassing Classical Assumption Tests, Multiple Linear Regression Analysis, and Hypothesis Testing. The result of this study indicate that profitability has effect and significant on Tax Avoidance, while firm size has not effect on tax avoidance. And simultaneously profitability and firm size have a significant effect on Tax Avoidance.